The creation of a new tourist destination in low density areas: the Boticas case - Lopes, Hélder (2016)
The goal of this paper is to contribute to identify a set of resources and tourism products, which can enhance the development and sustainability of tourism in the low density municipality of Boticas, located in the north-east of Portugal. Therefore, this paper tries to: i) produce a first analysis of the tourism potential of the municipality of Boticas; and ii) identify different perceptions of different stakeholders regarding the tourism potential of Boticas. To this end, the content analysis of semi-structured interviews conducted in 2014 to local and regional social and political stakeholders were used. Likewise, in 2015 two focus groups were conducted with main local stakeholders. The results highlight three main facts: first, there are unexplored tourism resources with potential to attract certain niches of tourist demand; second, the region has been investing in the diversification of its supply of leisure and recreational activities, as well as available tourism equipment; and third, the region is facing serious difficulties in creating a local and regional stakeholder network in order to provide an integrated promotion of tourism. We conclude by identifying few policy recommendations on development issues for the municipality of Boticas or other rural areas presenting similar constraints.